Research of basic models of transfer of intellectual and innovative technologies and directions of their development - Pererva, P. G.; Ievsieiev, A. S. (Wyższa Szkoła Ekonomiczno-Humanistyczna, Poland, 2023)
The article examines various forms and methods of transfer of intellectual technologies in the period from 1950 to the present time. It is substantiated that at different stages of social development, the ways of transferring intellectual technologies are different. At the initial stage, technology transfer was mainly carried out on the basis of agreements between top managers. After the industrial revolution, these processes were implemented at the expense of mandatory external investments in production capital. Today, technology transfer is mainly carried out through market-oriented commercial forms. Thus, technology transfer increasingly demonstrates its unique market-oriented characteristics, the specific features of which can be manifested in the following types and characteristics.
Дослідження основних моделей трансферу інтелектуальних та інноваційних технологій та напрямів їх розвитку
Keywords: technology transfer; commercialization; methods and models; use; technological market; industrial enterprises